Genome editing in maize and sorghum: A comprehensive review of CRISPR/Cas9 and emerging technologies - Mercy Jocyline Namata; Jingyi Xu; Ephrem Habyarimana; Sudhakar Reddy Palakolanu; Lihua Wang; Jieqin Li (The Plant Genome)
Abstract The increasing changes in the climate patterns across the globe have deeply affected food systems where unparalleled and unmatched challenges are created. This jeopardizes food security due to an ever‐increasing population. The extreme efficiency of C4 crops as compared to C3 crops makes them incredibly significant in securing food safety. C4 crops, maize (Zea mays L.) and sorghum (Sorghum bicolor L. Moench) in particular, have the ability to withstand osmotic stress induced by oxidative stress. Osmotic stress causes a series of physical changes in a plant thus facilitating reduced water uptake and photosynthesis inhibition, such as membrane tension, cell wall stiffness, and turgor changes. There has been a great advancement in plant breeding brought by introduction of clustered regularly interspaced short palindromic repeats (CRISPR) gene editing technology. This technology offers precise alterations to an organism's DNA through targeting specific genes for desired traits in a wide number of crop species. Despite its immense opportunities in plant breeding, it faces limitations such as effective delivery systems, editing efficiency, regulatory concerns, and off‐target effects. Future prospects lie in optimizing next‐generation techniques, such as prime editing, and developing novel genotype‐independent delivery methods. Overall, the transformative role of CRISPR/Cas9 in sorghum and maize breeding underscores the need for responsible and sustainable utilization to address global food security challenges.